Novae as supersoft X-ray sources in the Andromeda galaxy - Henze, M.; Pietsch, W.; Haberl, F.; Della Valle, M.; Sala, G.; Hatzidimitriou, D.; Hofmann, F.; Hernanz, M.; Hartmann, D.; Greiner, J. (2014)
Novae are the major class of supersoft X-ray sources (SSSs) in the central region of our neighbouring galaxy Andromeda (M31). From 2006 until 2012 we carried out a dedicated monitoring of the M31 central region with XMM-Newton and Chandra that was specifically designed to detect and characterise SSS states of novae. Only X-ray observations allow us to observe the hot post-nova white dwarf directly and study its physics. Here, I present new results based on an updated catalogue of 79 novae with SSS counterparts, which is by far the largest sample known in any galaxy, to date. Global trends and correlations were established between various multiwavelength nova parameters and there appear to be significant deviations from current models of Galactic novae. Furthermore, there is evidence for different X-ray parameters of sub-samples associated with the M31 bulge and disk, although the question whether both populations are inherently different is far from resolved. The sample contains several remarkable individual novae and I will discuss their peculiarities and importance. The X-ray monitoring of large, homogeneous samples of extragalactic novae is shown to be a powerful tool to study nova populations and the dependence of their observable characteristics on the underlying stellar population.